Enthesitis in a 16-Year-Old Boy with M694V Mutation - Syert Luidolf Nienhuis; Robin Eric Westerbeek (Case Reports in Medicine)
Introduction. FMF (Familial Mediterranean Fever) is characterized by recurrent attacks of fever and articular pain. Enthesitis is the hallmark of pain in spondyloarthropathy. Literature suggests association of M694V mutation and enthesitis. We report a case of a 16-year-old boy with enthesitis and FMF. Case Presentation. A 16-year-old boy of Turkish origin with a history of FMF presented with localized tenderness of the heel and severe disability. MRI showed an enthesitis of the plantar fascia. Standard treatment of FMF and enthesitis was not successful. After referral to a university hospital and expert opinion of a professor in rheumatology, this enthesitis should be treated as an enthesitis related arthritis. With this treatment, our patient fully recovered 8 months after the onset of the disease symptoms. Conclusion. M694V mutation related enthesitis should be considered in FMF patients with enthesitis. We would suggest treatment for enthesitis related arthritis in similar cases. This is of clinical importance because the treatment is different from treatment of enthesitis or articular pain caused by FMF.